Composite hydrogel for tissue repair as well as preparation method and application thereof

By preparing a composite hydrogel composed of methacrylated decellularized matrix, nanoclay and carboxymethyl chitosan, the problems of insufficient mechanical strength and uncontrollable degradation rate of small intestinal tissue repair materials were solved, the antibacterial and anti-inflammatory functions were achieved, and the repair and regeneration of small intestinal tissue were promoted.

CN120605377APending Publication Date: 2025-09-09YICHU (HANGZHOU) MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510782151.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-12
Publication Date
2025-09-09

AI Technical Summary

Technical Problem

Existing small intestinal tissue repair materials have problems such as insufficient mechanical strength, uncontrollable degradation rate and lack of antibacterial and anti-inflammatory functions, and there is still a gap in the research on the integration of carboxymethyl chitosan in small intestinal tissue engineering scaffolds.

Method used

A composite hydrogel composed of methacrylated decellularized matrix, nanoclay, photoinitiator and carboxymethyl chitosan is formed through chemical modification and physical cross-linking to form a scaffold material with excellent mechanical properties, controllable degradation rate and antibacterial and anti-inflammatory functions.

Benefits of technology

It improves the matching of the mechanical strength and degradation cycle of the hydrogel, provides a stable mechanical environment, reduces the risk of infection, promotes cell growth and tissue repair, and improves the success rate of tissue repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120605377A_ABST
    Figure CN120605377A_ABST
Patent Text Reader

Abstract

The invention relates to composite hydrogel for tissue repair as well as a preparation method and application of the composite hydrogel. The composite hydrogel is prepared from a methacrylated acellular matrix, nano clay (LAP), a photoinitiator, carboxymethyl chitosan (CMCS) and water. The acellular matrix is modified through methylacryloylation, and a polymer network is reinforced by combining nano-clay, so that the mechanical strength is improved; and carboxymethyl chitosan adjusts the degradation rate, constructs a pore structure and endows antibacterial and anti-inflammatory functions. The preparation method comprises the following steps: dissolving the methacrylated acellular matrix in the PBS containing the photoinitiator, dissolving the carboxymethyl chitosan in ultrapure water, mixing, and carrying out illumination cross-linking curing. When the composite hydrogel is applied to small intestine tissue engineering, a small intestine defect part can be filled with the composite hydrogel, photo-crosslinking curing is performed to form a stent, the degradation period is matched with the small intestine regeneration period, and the antibacterial rate is gt; the cell toxicity is 0 level, a good microenvironment can be provided for cells, tissue repair can be promoted, and the compound can also be used for preparing pharmaceutical compositions for treating small intestine related diseases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biological tissue repair, and in particular to a composite hydrogel for tissue repair, a preparation method thereof and an application thereof. Background Art

[0002] Repairing small intestinal tissue defects caused by trauma, surgical resection, or disease is a major clinical challenge. Traditional tissue repair methods (such as autologous or allogeneic transplantation) have problems such as insufficient donors, donor site complications, and disease transmission. Therefore, the use of bioengineering methods to achieve tissue repair has become a cutting-edge solution. By constructing a three-dimensional porous scaffold with biological activity and appropriate mechanical support, it is possible to provide cells with a natural growth environment and scaffold, promoting cell adhesion, proliferation, and differentiation, thereby accelerating the repair and regeneration of damaged tissue.

[0003] Acellular matrix materials are widely used as scaffolds for tissue engineering because they retain the three-dimensional structure and bioactive components of the natural extracellular matrix (ECM), such as collagen and growth factors. However, existing small intestinal acellular matrix hydrogels generally suffer from insufficient mechanical strength, uncontrollable degradation rates, and lack of antibacterial and anti-inflammatory properties.

[0004] Carboxymethyl chitosan (CMS) has excellent biocompatibility and cell adhesion-promoting properties, making it widely used in wound dressings. Its incorporation into small intestinal tissue engineering scaffolds offers hemostatic, antibacterial, and anti-inflammatory properties, while also preventing tissue adhesion. However, its integration into small intestinal tissue engineering scaffolds remains largely unexplored, and balancing its antibacterial and cytotoxic properties remains a technical challenge. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a composite hydrogel for tissue repair and a preparation method and application thereof, so as to provide a composite hydrogel for tissue repair and a preparation method and application thereof.

[0006] The present invention is achieved by providing a composite hydrogel for tissue repair, comprising the following components:

[0007] Methacrylated decellularized matrix: the decellularized matrix is ​​chemically modified by methacrylic anhydride, wherein the mass ratio of the decellularized matrix to methacrylic anhydride is 1:(0.5-0.7);

[0008] Nanoclay (LAP): It is mixed with methacrylated acellular matrix in a mass ratio of 1:(6.67-20) and is used as a physical or non-covalent crosslinker to strengthen the polymer network. It also releases bioactive ions during degradation to promote tissue repair.

[0009] Photoinitiator: one or more selected from lithium phenyl-2,4,6-trimethylbenzoylphosphinate or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, wherein the mass ratio of the photoinitiator to the methacrylated acellular matrix is ​​(0.05-0.2):1;

[0010] Carboxymethyl chitosan (CMCS): used to adjust the material degradation rate and construct the pore structure of the scaffold, the mass ratio of the carboxymethyl chitosan (CMCS) to the methacrylated decellularized matrix is ​​(20-100):1;

[0011] Water: used as a solvent to dissolve the components, so that the components are fully dissolved and form a uniform solution. The mass ratio of the carboxymethyl chitosan (CMCS) to water is 1: (10-15).

[0012] Furthermore, the compression modulus of the composite hydrogel is 100-200 kPa, the degradation period is 2-3 weeks, the antibacterial rate is greater than 90%, and the cytotoxicity is level 0.

[0013] A method for preparing a composite hydrogel for tissue repair comprises the following steps:

[0014] Step 1: dissolving the methacrylated acellular matrix powder in phosphate buffered saline (PBS) containing a photoinitiator and stirring thoroughly to dissolve it completely to obtain a photocrosslinked hydrogel precursor solution;

[0015] Step 2: Weigh carboxymethyl chitosan (CMCS) and add it to ultrapure water at 40°C. Continue stirring until the carboxymethyl chitosan is completely dissolved to form a uniform carboxymethyl chitosan solution.

[0016] Step 3: Weigh the carboxymethyl chitosan solution and nanoclay (LAP) obtained in step 2 and add them to the photocrosslinked hydrogel precursor solution obtained in step 1. Mix well and then crosslink and cure under 405 nm light, i.e., light intensity of 50 mW / cm 2 , distance 10 cm, cross-linking time 30 s to form a composite hydrogel.

[0017] Furthermore, the methacrylated decellularized matrix is ​​a methacrylated small intestine decellularized matrix, which is obtained by chemically modifying a small intestine decellularized matrix (SIS) with methacrylic anhydride, wherein the small intestine decellularized matrix (SIS) is obtained by the following steps:

[0018] First, collect fresh small intestinal tissue, preferably from pathogen-free animals;

[0019] The collected small intestinal tissue is then cut into samples of appropriate size;

[0020] Subsequently, the samples were immersed in a 0.5% TritonX-100 solution as an eluent for 4 to 7 hours, and an ultrasound-assisted decellularization process was used.

[0021] After the decellularization process is completed, the solution containing TritonX-100 is filtered out;

[0022] Afterwards, the samples were soaked in deionized water for 2 h;

[0023] After the soaking is completed, the sample is soaked in a 1% SDS solution for 0.5 to 2 hours.

[0024] Finally, the sample was rinsed with deionized water for 20 to 30 hours to completely remove the residual chemical detergents, thereby obtaining the small intestinal decellularized matrix (SIS).

[0025] Furthermore, the methacrylated small intestine acellular matrix is ​​obtained by the following steps:

[0026] adding the small intestine decellularized matrix (SIS) into a hydrochloric acid pepsin solution for treatment, freeze-drying, and grinding into powder;

[0027] Resuspend the powder in 0.1 M phosphate buffer and adjust the pH of the system to 8-9. After the temperature returns to normal, slowly add methacrylic anhydride dropwise and react at 4°C in the dark for 4-6 hours.

[0028] Finally, the product was dialyzed with a dialysis membrane and freeze-dried to obtain methacrylylated small intestinal decellularized matrix powder (SISMA).

[0029] A 3D bioprinted small intestine repair membrane is prepared from a composite hydrogel for tissue repair by the following steps:

[0030] adding gelatin to the composite hydrogel at a mass ratio of 10:(0.4-0.7) and dissolving the composite hydrogel at 35-45° C. to form a bio-ink;

[0031] The bio-ink was loaded into the 3D bio-printer, and the printing parameters were: nozzle temperature 20 °C, platform temperature 15 °C, printing speed 2 mm / s, and extrusion speed 0.35 mm. 3 / s;

[0032] After printing and molding, the porous small intestine repair material was obtained by cross-linking with 405nm blue light for 30 seconds.

[0033] Furthermore, the porous small intestine repair material has a pore size of 100 to 300 μm and a porosity of 60% to 80%.

[0034] A composite hydrogel for tissue repair is used in small intestinal tissue engineering. The specific application steps of the composite hydrogel for tissue repair for regeneration and repair of small intestinal defects are as follows:

[0035] The composite hydrogel is filled into the defect site of the small intestine and solidified by photocrosslinking to form a scaffold;

[0036] The scaffold releases growth factors to promote myoblast adhesion, proliferation and differentiation, and its degradation rate is synchronized to match the small intestine regeneration cycle.

[0037] A pharmaceutical composition comprises the composite hydrogel for tissue repair, and is used for treating small intestinal trauma, postoperative defects or post-intestinal infarction repair.

[0038] Compared with the prior art, the present invention provides a composite hydrogel for tissue repair, a preparation method thereof, and an application thereof. The composite hydrogel for tissue repair comprises the following components: a methacrylated decellularized matrix, nanoclay (LAP), a photoinitiator, and carboxymethyl chitosan (CMCS);

[0039] The addition of nanoclay strengthens the polymer network and significantly enhances the mechanical strength of the composite hydrogel, enabling it to better withstand the various mechanical stresses during intestinal tissue repair. This provides a more stable mechanical environment for cell growth and tissue repair, helping to promote the repair and regeneration of damaged tissue. The addition of carboxymethyl chitosan aligns the degradation cycle of the composite hydrogel with the intestinal regeneration cycle, preventing premature degradation from damaging the scaffold structure, which could affect cell adhesion and tissue repair, and preventing slow degradation from hindering the growth and integration of new tissue, thereby ensuring a smooth repair process. Furthermore, carboxymethyl chitosan imparts excellent antibacterial and anti-inflammatory properties to the composite hydrogel, with an antibacterial rate of >90%. This effectively reduces the risk of infection during intestinal tissue repair and minimizes the interference of inflammatory responses on tissue repair, creating more favorable conditions for cell growth and tissue regeneration, and accelerating the repair process of damaged tissue. The composite hydrogel exhibits a cytotoxicity level of 0, indicating its non-toxicity and excellent biocompatibility. This allows cells to better adhere, proliferate, and differentiate within the "microenvironment" provided by the composite hydrogel, promoting cell growth and tissue repair, and improving the success rate of tissue repair.

[0040] The small intestinal decellularized matrix hydrogel is prepared from methacrylated small intestinal decellularized matrix and a photoinitiator. The present invention first performs methacrylation on the small intestinal decellularized matrix to give it photocrosslinking gelling properties, which can improve the rheological properties of the photocrosslinked small intestinal decellularized matrix hydrogel and enhance its mechanical stability. At the same time, the small intestinal decellularized matrix hydrogel has the environmental characteristics of simulating the extracellular matrix of bladder tissue, does not cause an immune response, and can provide an extracellular matrix "microenvironment" for cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 A composite hydrogel for tissue repair according to the present invention, and a preparation method and application diagram thereof;

[0042] Figure 2 Appearance morphology of the acellular matrix composite hydrogel prepared in an embodiment of the present invention;

[0043] Figure 3 FTIR image of the decellularized matrix prepared in an embodiment of the present invention;

[0044] Figure 4 FTIR image of the composite hydrogel prepared in Example of the invention;

[0045] Figure 5 The swelling ratio of the acellular matrix hydrogel prepared in the embodiment of the present invention;

[0046] Figure 6 The compressive strength of the acellular matrix hydrogel prepared in the embodiment of the present invention;

[0047] Figure 7 Degradation time of the acellular matrix hydrogel prepared in the embodiment of the present invention. DETAILED DESCRIPTION

[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0049] A composite hydrogel for tissue repair, comprising the following components:

[0050] Methacrylated decellularized matrix: the decellularized matrix is ​​chemically modified by methacrylic anhydride, wherein the mass ratio of the decellularized matrix to methacrylic anhydride is 1:(0.5-0.7);

[0051] Nanoclay (LAP): The mixing mass ratio of nanoclay (LAP) to methacrylated decellularized matrix is ​​1: (6.67-20), and it is used as a physical or non-covalent crosslinker to strengthen the polymer network. At the same time, it releases bioactive ions during the degradation process to promote tissue repair. By introducing nanoclay (LAP), it is mixed with methacrylated decellularized matrix in a specific mass ratio and used as a physical or non-covalent crosslinker to strengthen the polymer network, effectively improving the mechanical properties of the composite hydrogel, so that the compression modulus of the composite hydrogel reaches 100-200kPa, solving the problem of insufficient mechanical strength of hydrogels in the existing technology and providing more reliable mechanical support for small intestinal tissue repair.

[0052] Photoinitiator: selected from one or more of lithium phenyl-2,4,6-trimethylbenzoylphosphinate or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, with the mass ratio of the photoinitiator to the methacrylated decellularized matrix being (0.05-0.2):1. By adding carboxymethyl chitosan (CMCS), the degradation rate of the material can be adjusted, so that the degradation cycle of the composite hydrogel is 2-3 weeks, which matches the regeneration cycle of the small intestine, avoids the impact of excessively fast or slow degradation rate on tissue repair, and solves the technical problem of uncontrollable degradation rate.

[0053] Carboxymethyl chitosan (CMCS): Used to regulate the material degradation rate and construct the pore structure of the scaffold. The mass ratio of carboxymethyl chitosan (CMCS) to methacrylated decellularized matrix is ​​(20-100):1. Integrating carboxymethyl chitosan (CMCS) into the composite hydrogel gives the material excellent antibacterial and anti-inflammatory properties, with an antibacterial rate of >90%, effectively reducing the risk of infection and promoting tissue repair and regeneration, making up for the shortcomings of existing technologies in this regard.

[0054] Water: used as a solvent to dissolve the components, so that the components are fully dissolved and form a uniform solution. The mass ratio of the carboxymethyl chitosan (CMCS) to water is 1: (10-15).

[0055] The composite hydrogel has a compression modulus of 100-200 kPa, a degradation period of 2-3 weeks, an antibacterial rate of more than 90%, and a cytotoxicity of level 0.

[0056] A method for preparing a composite hydrogel for tissue repair comprises the following steps:

[0057] Step 1: dissolving the methacrylated acellular matrix powder in phosphate buffered saline (PBS) containing a photoinitiator and stirring thoroughly to dissolve it completely to obtain a photocrosslinked hydrogel precursor solution;

[0058] Step 2: Weigh carboxymethyl chitosan (CMCS) and add it to ultrapure water at 40°C. Continue stirring until the carboxymethyl chitosan is completely dissolved to form a uniform carboxymethyl chitosan solution.

[0059] Step 3: Weigh the carboxymethyl chitosan solution and nanoclay (LAP) obtained in step 2 and add them to the photocrosslinked hydrogel precursor solution obtained in step 1. After mixing evenly, crosslink and cure under 405 nm light to form a composite hydrogel.

[0060] The methacrylated decellularized matrix is ​​a methacrylated small intestine decellularized matrix, which is obtained by chemically modifying the small intestine decellularized matrix (SIS) with methacrylic anhydride, wherein the small intestine decellularized matrix (SIS) is obtained by the following steps: first, fresh small intestine tissue is collected, preferably small intestine tissue of a pathogen-free animal; then, the collected small intestine tissue is cut into samples of appropriate size; then, a TritonX-100 solution with a mass fraction of 0.5% is used as an eluent to soak the sample for a soaking time of 4 to 7 hours, and an ultrasound-assisted decellularization process is used at the same time; after the decellularization treatment is completed, the solution containing TritonX-100 is filtered out; then, the sample is soaked in deionized water for 2 hours; after the soaking is completed, the sample is soaked in a 1% SDS solution with a mass fraction for a soaking time of 0.5 to 2 hours; finally, the sample is rinsed with deionized water for 20 to 30 hours to completely remove residual chemical detergents, thereby obtaining the small intestine decellularized matrix (SIS). Triton X-100 solution refers to Triton X-100 or polyethylene glycol octylphenyl ether solution; SDS solution refers to that containing sodium dodecyl sulfate.

[0061] The methacrylated small intestine decellularized matrix is ​​obtained by the following steps: adding the small intestine decellularized matrix (SIS) to a hydrochloric acid pepsin solution for treatment, freeze-drying and grinding into powder; resuspending the powder in a 0.1M phosphate buffer, and adjusting the pH of the system to 8-9, slowly adding methacrylic anhydride dropwise after the temperature is restored, and reacting at 4°C in the dark for 4-6 hours; finally, dialyzing with a dialysis membrane and freeze-drying to obtain methacrylated small intestine decellularized matrix powder (SISMA).

[0062] A 3D bioprinted small intestine repair membrane is prepared from a composite hydrogel for tissue repair by the following steps: adding gelatin to the composite hydrogel, with a mass ratio of the composite hydrogel to gelatin of 10:(0.4-0.7), and dissolving at 35-45°C to form a bio-ink; loading the bio-ink into a 3D bioprinter, and using the following printing parameters: nozzle temperature of 20°C, platform temperature of 15°C, printing speed of 2 mm / s, and extrusion speed of 0.35 mm 3 After printing and forming, the porous small intestine repair material is cross-linked by 405nm blue light for 30 seconds to obtain a porous small intestine repair material with a pore size of 100 to 300 μm and a porosity of 60% to 80%.

[0063] A composite hydrogel for tissue repair is used in small intestinal tissue engineering. The specific application steps of the composite hydrogel for tissue repair for regenerative repair of small intestinal defects are as follows: the composite hydrogel is filled in the defect site of the small intestine and solidified by photocrosslinking to form a scaffold; the scaffold releases growth factors to promote myoblast adhesion, proliferation and differentiation, and the synchronous degradation rate matches the small intestinal regeneration cycle.

[0064] A pharmaceutical composition comprises the composite hydrogel for tissue repair, and is used for treating small intestinal trauma, postoperative defects or post-intestinal infarction repair.

[0065] Example

[0066] Example 1: 20 g of small intestinal tissue was weighed and cut into 1-2 cm small intestinal tissue fragments. 100 mL of 0.5% Triton X-100 reagent was added and soaked for 6 hours. The detergent was filtered out using a filter membrane, and then 200 mL of deionized water was added and soaked for 2 hours. After removing the deionized water, 100 mL of 1% SDS was added and soaked for 1 hour. After filtering out the SDS, the detergent was rinsed with deionized water to remove the detergent. The small intestinal decellularized matrix was obtained, and pepsin hydrochloride solution was added and soaked for 1 hour. The enzyme solution was filtered out and the fragment was vacuum-lyophilized. After lyophilization, the fragment was ground into a powder using a ball mill. The powder was dispersed in sodium carbonate solution at pH 8. After returning to room temperature, methacrylic anhydride was added and reacted in the dark for 24 hours. After the reaction, the fragment was dialyzed using a dialysis membrane and re-lyophilized to obtain a powder, which is the methacrylated small intestinal decellularized matrix powder of the present invention.

[0067] Example 2: 20 g of small intestinal tissue was weighed and cut into 1-2 cm small intestinal tissue fragments. 100 mL of 1% Triton X-100 reagent was added and soaked for 4 hours. The detergent was filtered out using a filter membrane, and then 400 mL of deionized water was added and soaked for 3 hours. After removing the deionized water, 200 mL of 1% SDS was added and soaked for 0.5 hours. After filtering out the SDS, the detergent was rinsed with deionized water. The resulting small intestinal decellularized matrix was lyophilized and ground into a powder using a ball mill. The powder was then soaked in a hydrochloric acid pepsin solution for 24 hours. The pH of the solution was adjusted to 6.0. Subsequently, methacrylic anhydride was added and reacted in the dark for 24 hours. After the reaction, the fragment was dialyzed using a dialysis membrane and re-lyophilized to obtain a powder, which is the methacrylated small intestinal decellularized matrix powder of the present invention.

[0068] Example 3: 4 g of carboxymethyl chitosan was weighed and dispersed in 50 mL of deionized water. Dissolved by stirring at 40°C to obtain a carboxymethyl chitosan solution. 1 g of methacrylated small intestinal acellular matrix powder was dissolved in 50 mL of the carboxymethyl chitosan solution. 0.05 g of photoinitiator was added and stirred evenly. 0.05 g, 0.1 g, or 0.15 g of nanoclay was added and stirred evenly. The mixture was then allowed to swell at room temperature for 80 minutes to obtain the composite hydrogel sample of the present invention.

[0069] Example 4: 10 mL of the composite hydrogel obtained in Example 3 was added with 0.5 g of gelatin, fully dissolved at 40°C, and connected to a 3D bioprinter. Printing parameters were: nozzle temperature 20°C, platform temperature 15°C, printing speed 2 mm / s, and extrusion speed 0.35 mm. 3 / s; after printing and molding, it was cross-linked by 405nm blue light for 30 seconds to obtain a porous small intestine repair material.

[0070] Experimental example

[0071] Experimental Example 1: Fourier transform infrared analysis was performed on the composite hydrogel and SISMA-CMCS of Example 3. The experimental results are as follows: Figure 4 As shown, the three groups of hydrogels with LAP added have a wavelength of 1100 cm -1 The COC characteristic peak of CMCS disappeared, indicating that cross-linking occurred between LAP and CMCS.

[0072] Experimental Example 2: The swelling ratio of the composite hydrogel of Example 3 was analyzed. The experimental results are as follows: Figure 5 As shown, LAP1, 2, and 3 represent the addition of nanoclay at different concentrations. It can be seen that the increase in the proportion of nanoclay promotes the increase in the swelling ratio of the hydrogel.

[0073] Experimental Example 3

[0074] The compressive strength test of the composite hydrogel of Example 3 was carried out respectively, and the experimental results are as follows: Figure 6 As shown in the figure, it can be seen that the increase in the proportion of nanoclay has a promoting effect on the increase of the compressive strength of the hydrogel.

[0075] Experimental Example 4: Degradation experiments were carried out on the composite hydrogel of Example 3. The experimental results are as follows: Figure 7 As shown, varying the nanoclay ratio alters the degradation rate, which can be adjusted based on the regeneration rate of the small intestine to prepare suitable small intestinal repair tissue. According to Experiments 2-4, nanoclay can regulate water absorption and degradation rate. Generally, selecting a moderate content maintains good mechanical properties while facilitating the cell repair process.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A composite hydrogel for tissue repair, characterized in that: It consists of the following components: Methacrylated decellularized matrix: the decellularized matrix is ​​chemically modified by methacrylic anhydride, wherein the mass ratio of the decellularized matrix to methacrylic anhydride is 1:(0.5-0.7); Nanoclay (LAP): It is mixed with methacrylated acellular matrix in a mass ratio of 1:(6.67-20) and is used as a physical or non-covalent crosslinker to strengthen the polymer network. It also releases bioactive ions during degradation to promote tissue repair. Photoinitiator: one or more selected from lithium phenyl-2,4,6-trimethylbenzoylphosphinate or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, wherein the mass ratio of the photoinitiator to the methacrylated acellular matrix is ​​(0.05-0.2):1; Carboxymethyl chitosan (CMCS): used to adjust the material degradation rate and construct the pore structure of the scaffold, the mass ratio of the carboxymethyl chitosan (CMCS) to the methacrylated decellularized matrix is ​​(20-100):1; Water: used as a solvent to dissolve the components, so that the components are fully dissolved and form a uniform solution. The mass ratio of the carboxymethyl chitosan (CMCS) to water is 1: (10-15).

2. The composite hydrogel for tissue repair according to claim 1, wherein The composite hydrogel has a compression modulus of 100-200 kPa, a degradation period of 2-3 weeks, an antibacterial rate of more than 90%, and a cytotoxicity of level 0.

3. A method for preparing a composite hydrogel for tissue repair, characterized in that: The following steps are involved: Step 1: dissolving the methacrylated acellular matrix powder in phosphate buffered saline (PBS) containing a photoinitiator and stirring thoroughly to dissolve it completely to obtain a photocrosslinked hydrogel precursor solution; Step 2: Weigh carboxymethyl chitosan (CMCS) and add it to ultrapure water at 40°C. Continue stirring until the carboxymethyl chitosan is completely dissolved to form a uniform carboxymethyl chitosan solution. Step 3: Weigh the carboxymethyl chitosan solution and nanoclay (LAP) obtained in step 2 and add them to the photocrosslinked hydrogel precursor solution obtained in step 1. After mixing evenly, crosslink and cure under 405 nm light to form a composite hydrogel.

4. The method for preparing the composite hydrogel for tissue repair according to claim 2, wherein: The methacrylated decellularized matrix is ​​a methacrylated small intestine decellularized matrix, which is obtained by chemically modifying a small intestine decellularized matrix (SIS) with methacrylic anhydride, wherein the small intestine decellularized matrix (SIS) is obtained by the following steps: First, collect fresh small intestinal tissue, preferably from pathogen-free animals; The collected small intestinal tissue is then cut into samples of appropriate size; Subsequently, the samples were immersed in a 0.5% TritonX-100 solution as an eluent for 4 to 7 hours, and an ultrasound-assisted decellularization process was used. After the decellularization process is completed, the solution containing TritonX-100 is filtered out; Afterwards, the samples were soaked in deionized water for 2 h; After the soaking is completed, the sample is soaked in a 1% SDS solution for 0.5 to 2 hours. Finally, the sample was rinsed with deionized water for 20 to 30 hours to completely remove the residual chemical detergents, thereby obtaining the small intestinal decellularized matrix (SIS).

5. The method for preparing the composite hydrogel for tissue repair according to claim 4, wherein: The methacrylated small intestine decellularized matrix is ​​obtained by the following steps: adding the small intestine decellularized matrix (SIS) into a hydrochloric acid pepsin solution for treatment, freeze-drying, and grinding into powder; Resuspend the powder in 0.1 M phosphate buffer and adjust the pH of the system to 8-9. After the temperature returns to normal, slowly add methacrylic anhydride dropwise and react at 4°C in the dark for 4-6 hours. Finally, the product was dialyzed with a dialysis membrane and freeze-dried to obtain methacrylylated small intestinal decellularized matrix powder (SISMA).

6. A 3D bioprinted small intestine repair membrane, characterized in that: The composite hydrogel for tissue repair according to any one of claims 1 to 5 is prepared by the following steps: adding gelatin to the composite hydrogel at a mass ratio of 10:(0.4-0.7) and dissolving the composite hydrogel at 35-45° C. to form a bio-ink; The bio-ink was loaded into the 3D bio-printer, and the printing parameters were as follows: nozzle temperature 20°C, platform temperature 15°C, printing speed 2 mm / s, and extrusion speed 0.35 mm. 3 / s; After printing and molding, the porous small intestine repair material was obtained by cross-linking with 405nm blue light for 30 seconds.

7. The 3D bioprinted small intestine repair membrane according to claim 6, characterized in that: The pore size of the porous small intestine repair material is 100-300 μm, and the porosity is 60%-80%.

8. Application of a composite hydrogel for tissue repair in small intestinal tissue engineering, characterized in that: The specific application steps of the composite hydrogel for tissue repair according to any one of claims 1 to 5 for regenerative repair of small intestinal defects are as follows: The composite hydrogel is filled into the defect site of the small intestine and solidified by photocrosslinking to form a scaffold; The scaffold releases growth factors to promote myoblast adhesion, proliferation and differentiation, and its degradation rate is synchronized to match the small intestine regeneration cycle.

9. A pharmaceutical composition, characterized in that The composite hydrogel for tissue repair according to any one of claims 1 to 5 is used to treat small intestinal trauma, postoperative defects or post-intestinal infarction repair.

Citation Information

Cited By

  • 3D printing high-strength supramolecular hydrogel and application thereof in bone defect repair

    CN121059891A